PhD Research in Humanities & Social Sciences: Methods & Approaches (Patan Pragya, 2022)
This paper discusses philosophical approaches usually employed in undertaking research in general and PhD research in particular in Humanities and Social Sciences. The role of qualitative research that focuses on feelings and opinions collected through different research methods and tools is paramount in disciplines like History, Economics, Sociology, Linguistics, Literature etc. The article underscores the approaches rather than methods. In addition, the paper demonstrates how approaches including positivism, constructivism, interpretivism, critical theory, and so on rest on the ontological, epistemological, and axiological postulates. The objective of the paper is to inform the researchers and scholars about the philosophical approaches used in conducting research in different disciplines in general and in Humanities and Social Sciences in particular. Besides, the paper brings quantitative research method into discussion to comprehensively present differences and purposes of both qualitative and quantitative approaches. The knowledge of both approaches and paradigms can help to employ the most appropriate approach in undertaking qualitative research. The finding shows that the philosophical approaches including positivism, post-positivism, interpretivism, constructivism, and critical theory are widely employed in social sciences. These pervade in almost all disciplines for analyzing both qualitative and quantitative data. However, interpretivism, constructivism, and critical theory are paramount in undertaking qualitative research.